Β-arrestin-biased agonism of β-adrenergic receptor regulates Dicer-mediated microRNA maturation to promote cardioprotective signaling. (May 2018) - Teoh, Jian-Peng; Bayoumi, Ahmed S.; Aonuma, Tatsuya; Xu, Yanyan; Johnson, John A.; Su, Huabo; Weintraub, Neal L.; Tang, Yaoliang; Kim, Il-Man
Abstract: Rationale: MicroRNAs (miRs) are small, non-coding RNAs that function to post-transcriptionally regulate target genes. First transcribed as primary miR transcripts (pri-miRs), they are enzymatically processed by Drosha into premature miRs (pre-miRs) and further cleaved by Dicer into mature miRs. Initially discovered to desensitize β-adrenergic receptor (βAR) signaling, β-arrestins are now well-appreciated to modulate multiple pathways independent of G protein signaling, a concept known as biased signaling. Using the β-arrestin-biased βAR ligand carvedilol, we previously showed that β-arrestin1 (not β-arrestin2)-biased β1AR (not β2AR) cardioprotective signaling stimulates Drosha-mediated processing of six miRs by forming a multi-protein nuclear complex, which includes β-arrestin1, the Drosha microprocessor complex and a single-stranded RNA binding protein hnRNPA1. Objective: Here, we investigate whether β-arrestin-mediated βAR signaling induced by carvedilol could regulate Dicer-mediated miR maturation in the cytoplasm and whether this novel mechanism promotes cardioprotective signaling. Methods and results: In mouse hearts, carvedilol indeed upregulates three mature miRs, but not their pre-miRs and pri-miRs, in a β-arrestin 1- or 2-dependent manner. Interestingly, carvedilol-mediated activation of miR-466g or miR-532-5p, and miR-674 is dependent on β2ARs and β1ARs, respectively. Mechanistically, β-arrestin 1 or 2 regulates maturation of three newly identified βAR/β-arrestin-responsive miRs (β-miRs) by associating with the Dicer maturation RNase III enzyme on three pre-miRs of β-miRs. Myocardial cell approaches uncover that despite their distinct roles in different cell types, β-miRs act as gatekeepers of cardiac cell functions by repressing deleterious targets. Conclusions: Our findings indicate a novel role for βAR-mediated β-arrestin signaling activated by carvedilol in Dicer-mediated miR maturation, which may be linked to its protective mechanisms. Graphical abstract: Highlights: Carvedilol promotes the Dicer-mediated miR maturation. Carvedilol-mediated miR maturation requires β-arrestin1 or 2 and β1 AR or β2 AR. β-arrestin 1 or 2 forms a novel complex with the Dicer maturation enzyme. βAR/β-arrestin-responsive miRs act as gatekeepers of myocardial cell functions. βAR/β-arrestin-responsive miRs repress DCUN1D4, PRSS23, and USP14 .